Oral Supplementation with Three Vegetable Oils Differing in Fatty Acid Composition Alleviates High-Fat Diet-Induced Obesity in Mice by Regulating Inflammation and Lipid Metabolism - Waleed Aldamarany; Huang Taocui; Deng Liling; Yang Wanfu; Geng Zhong (Polish Journal of Food and Nutrition Sciences)
Obesity has become one of the most prevalent chronic diseases worldwide, which affects people's health and daily lives. Therefore, this study aimed to investigate the anti-obesity effects of perilla seed oil (PSO), sunflower oil (SFO), and tea seed oil (TSO) and their potential mechanisms in mice fed a high-fat diet (HFD). Mice were divided into five groups: ND, mice fed a normal diet; HFD, mice fed a high-fat diet; PSO, SFO, and TSO, mice fed a high-fat diet supplemented with PSO, SFO, and TSO at 2 g/kg body weight per day, respectively. Our findings showed that oral supplementation with all three oils for 8 weeks significantly reduced body weight, tissue weight, insulin resistance index, serum levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), and free fatty acids (FFA), and markedly alleviated hyperglycemia, hyperlipidemia, and hepatic steatosis in obese mice. It also decreased leptin, pro-inflammatory cytokines, such as tumor necrosis factor-alpha (TNF-α), interleukin (IL)-6, and (IL)-1beta (IL-1β), and increased anti-inflammatory adipokine adiponectin at both secretion and mRNA expression levels in the epididymal adipose tissue (EAT). Moreover, PSO, SFO, and TSO administration increased the expression levels of fatty acid β-oxidation-related genes, including peroxisome proliferator-activated receptor-alpha (PPAR-α), carnitine palmitoyltransferase 1a (CPT1a) and CPT1b, and thermogenesis-related genes such as uncoupling protein 1 (UCP1), and decreased the expression levels of lipid synthesis-related genes, including fatty acid synthase (FAS) and PPAR-γ in EAT. In conclusion, PSO, SFO, and TSO supplementation could have potential anti-obesity effects in HFD-fed mice by reducing inflammation and improving lipid metabolism.